Arts-based Learning Model with Clay to Instill Aesthetic Sensitivity of Visual Impairment Children - Nur Fajrie, Murtono, Tjetjep Rohendi Rohidi, Syakir; Ibnan Syarif (International Journal of Advanced Science and Technology, 2020)
This study aims to describe the art learning approach using clay media for children with visual impairments. An artistic approach through art-based research focuses on the exploration of ideas, the interpretation of narratives, conceptual development and the implementation of artistic creations. The study participants consisted of two low vision children, one blind child and two blind children. The results of the study found the concept of learning art for children with visual impairments that consider the characteristics of aesthetic needs. Art experiences can be seen in the activities of appreciation and artistic creation in the self-perception of the environment as a learning approach. Appropriate learning technique is the ability to add and subtract art material. Learning media on clay material is very suitable based on nature and character used. Artwork created can train sensory sensitivity possessed through the activities of holding, recognizing, knowing, identifying and expressing opinions.